Job satisfaction influenced by training satisfaction: an empirical study of university employees - Jan, Muhammad Tahir; Jager, Johan W de (GMP Press and Printing, 2025)
The aim of this research is to establish a framework that assesses the factors that influence job satisfaction, specifically through the lens of training among university employees. A comprehensive instrument was developed based on various established studies that encompassed all variables of the research. The data collected from the respondents were analysed using SPSS software, and reliability tests and regression analysis were carried out to determine the relationship between all training factors and job satisfaction. The study revealed that all of the overall training dimensions had a positive correlation with training satisfaction in terms of job satisfaction. This research is significant as it contributes to the development of training and employee development strategies in universities. Previous research has largely focused on the effects of training in other industries, with very few studies investigating the relationship between job satisfaction and training satisfaction in higher learning institutions. Job satisfaction is a crucial aspect that impacts employee motivation, commitment, and productivity, and it is influenced by various factors, including training. Employee training and development programs play a significant role in enhancing employee skills, knowledge, and performance, which consequently leads to increased job satisfaction. This study has provided valuable insights into the relationship between training satisfaction and job satisfaction, highlighting the importance of investing in employee training and development programs for the overall success of universities.